Qualitative detection: Adulterants and preservatives in raw vis-Ã -vis packaged milk marketed in and around Guwahati city - Kakati, Smita; Talukdar, Archana; Hazarika, Razibuddinahmed; Raquib, Masuk; Laskar, Saurabh (Indian Journal of Animal Production and Management, 2018)
An investigation was carried out to monitor the presence of adulterants and preservatives of raw pooled milk vis-a-vis pasteurized packaged milk sold in and around Guwahati city. A total 200 raw pooled milk samples and 5 branded pasteurized packaged milk samples were randomly collected to qualitatively determine the presence of various adulterants and preservatives. The results of present study revealed that the percent adulteration of different adulterants and preservative in raw pooled milk, it was 11, 9, 6 and 2%for the presence of water, neutralizers, salt and ammonia, respectively. None of the samples were positive for presence of other adulterants and preservatives such as starch, cane sugar, cereal flour, glucose, hydrogen peroxide, urea and formalin. The study indicates that there is trend of adulteration of raw milk sold with cheaper and easily available ingredients in different parts of Guwahati city thereby affecting the nutritive value of milk and may be a concern of public health.